Groundtruthing nitrogen isotopes as a symbiosis proxy using the facultatively symbiotic coral Oculina arbuscula - Donnelly, Heather A.; Valadez-Ingersoll, Maria; Lin, Marcus; Rivera, Hanny E.; Tramonte, Carlos A.; Davies, Sarah W.; Wang, Xingchen Tony (Frontiers in Marine Science, 2024)
The resilience of coral reefs in oligotrophic, (sub)tropical oceans is largely due to the symbiotic relationship between scleractinian corals and Symbiodiniaceae algae, which enables efficient internal nutrient recycling. Investigating the history of this coral symbiosis can provide insights into its role in sustaining the health of both present and future coral reefs. The isotopic composition of organic nitrogen (15N/14N or δ15N) bound within coral skeletons has been utilized to trace the existence of symbiosis in fossil corals, suggesting that coral symbiosis dates back to at least 210 million years ago. The basis of this proxy is that symbiotic corals are expected to exhibit lower δ15N compared to their non-symbiotic (aposymbiotic) counterparts within the same environments, owing to internal nitrogen recycling between the coral host and algal symbiont, and reduced leakage of low-δ15N ammonium into seawater. However, this hypothesis has not been adequately tested in contemporary settings. In a laboratory experiment, we examined the δ15N differences between the symbiotic and aposymbiotic branches within the same genetic backgrounds of the facultatively symbiotic coral Oculina arbuscula under well-fed conditions. Across five different genotypes in two separate experiments, symbiotic branches consistently showed lower δ15N than their aposymbiotic counterparts. These findings corroborate the use of δ15N as a proxy for identifying coral symbiosis in the past, particularly when multiple species of corals coexisted in the same environments.